2020
DOI: 10.5198/jtlu.2020.1692
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the combined effect of shared autonomous vehicles and congestion pricing on regional job accessibility

Abstract: Most of the existing research on shared autonomous vehicles (SAVs) and road congestion pricing have studied the short-term impact on traffic flow. These types of studies focused on the influences on mobility and ignored the long-term impacts on regional job accessibility. Given this, from the perspective of land use and transportation integration, this study explored the long-term effects of SAVs and cordon-based congestion pricing on regional land use, transportation, and job accessibility. The contributions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 54 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…One latest study revealed that 10% of survey respondents were willing to move farther from the city center in the presence of AVs and SAVs in the next few years, while 15% of the survey respondents indicated that they would likely move closer to the city center, which has an impact on travel behavior and land use [7]. e initiation of SAVs also offers an opportunity for employment and business growth in the charging zone and reduces the adverse impact of road congestion pricing [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One latest study revealed that 10% of survey respondents were willing to move farther from the city center in the presence of AVs and SAVs in the next few years, while 15% of the survey respondents indicated that they would likely move closer to the city center, which has an impact on travel behavior and land use [7]. e initiation of SAVs also offers an opportunity for employment and business growth in the charging zone and reduces the adverse impact of road congestion pricing [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…e increase in VMT can be a cause of congestion and therefore impedes sustainable urban development [16]. A recent study suggests that SAVs can create bottlenecks for other road users by stopping on the curbside to take and drop passengers [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, as the price of the private car became much cheaper, carsharing turned to be less attractive until the rising fuel prices and heavy road congestion have drawn the public's attention back to carsharing [8]. In recent years, shared mobility becomes a hot topic in transport development, and so does electrification [12,16,17]. Electric carsharing, a form of carsharing which rents EVs to people, combines these two items and is expected to inherit their positive impacts on sustainable transport development, including guiding the public to form a sustainable travel behavior [6], improving the accessibility and flexibility of the urban transport [12], reducing car ownership [5], vehicle kilometres of travel [9], traffic congestion [18], parking land use [18], and greenhouse gas emissions [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhong et al evaluated the long-term impacts of congestion pricing, as well as shared AVs, on job accessibility, transportation, and land, use. They revealed that introducing shared AVs reduced the negative effects of road congestion pricings and contributed to population development as well as job in charging zones 36 . Dianin et al conducted a study to represent a framework for important and developing aspects regarding AV implication of accessibility as well as transport equities.…”
Section: Introductionmentioning
confidence: 99%